Selenium and tellurium in Reykjanes Ridge and Icelandic basalts: Evidence for degassing-induced Se isotope fractionation - Yierpan, A.; Redlinger, J.; König, Stephan (Geochimica et Cosmochimica Acta, 2021)
Selenium behaves as a chalcophile and moderately volatile element during planetary accretion and magmatic processes on Earth. Together with the geochemically similar S and Te, Se is more volatile than most other moderately volatile elements and thus potentially becomes a new tracer to constrain the mechanism of volatile depletion in the Earth's mantle and other planetary bodies. As previously observed for several volatile elements, stable isotopes of Se are expected to fractionate upon eruptive outgassing of magmas. To understand the degassing behavior of Se and associated isotope fractionation, we report on Se and Te contents and Se isotope compositions (δSe) of submarine glasses across a range of distant ridge depth intervals along the Reykjanes Ridge and subglacial/subaerial basalts on Iceland (51–65°N; N = 22). Selenium (150–399 ng/g) and Te (2.61–14.5 ng/g) contents of the submarine glasses display progressive enrichment along the Reykjanes Ridge towards Iceland. This can be explained either by enhanced mantle melting towards Iceland or by enrichment of Se–Te contents in the mantle source due to the Icelandic plume–Reykjanes Ridge interaction. Both scenarios are equally plausible. The δSe values of submarine Reykjanes Ridge glasses range between −0.20 ± 0.08‰ and −0.08 ± 0.08‰ (on average −0.15 ± 0.07‰; 2SD, N = 15), which are unaffected by the Icelandic plume contribution and remain strictly within the previously reported average for depleted MORBs. These new data combined with literature δSe for depleted MORBs define a highly homogeneous depleted mantle composition δSe = −0.15 ± 0.11‰ (2SD, N = 44). On the other hand, we observed degassing of Se and Te to a variable extent (~40–95%) in submarine Reykjanes glasses at depths shallower than ~250 m and in subaerial/subglacial basalts on Iceland. Degassing-induced Se isotope fractionation shifted δSe of subaerial lavas towards heavier values (by up to ~0.44‰) well outside the range of submarine MORBs. However, when Se outgassing is associated with subglacial ...